Neoadjuvant anti-programmed death-1 immunotherapy by Pembrolizumab in resectable nodal positive stage II/IIIa non-small-cell lung cancer (NSCLC): the NEOMUN trial - Eichhorn, Florian; Klotz, Laura Valentina; Bischoff, Helge; Thomas, Michael; Lasitschka, Felix; Winter, Hauke; Hoffmann, Hans; Eichhorn, Martin E. (BMC cancer, 2019)
Immunotherapies targeting the PD1/PD-L1 pathway have had a large impact on the treatment of advanced NSCLC. Concerning multimodality tumor therapy, only few trials until today have been performed investigating neoadjuvant treatment with anti PD-1 immunotherapy prior to curative intent surgery. Aim of the NEOMUN investigator initiated trial (EudraCT-Number: 2017-000105-20; ClinicalTrials.govIdentifier: NCT03197467) is to assess feasibility and safety of pre-surgical anti PD-1 treatment in order to improve long term survival.
Gesehen am 10.03.2020